Environment-friendly flame-retardant cellulose nanofiber triboelectric nanogenerator and preparation method and application thereof
By combining straw recycling resources to prepare cellulose nanofibers with micro/sodium-level two-dimensional flame retardant fillers, using fluid directional assembly technology, the fire risk and complex preparation problems of cellulose triboelectric materials are solved, and efficient and environmentally friendly Flame-retardant cellulose nanogenerator with excellent triboelectric and flame retardant properties.
Patent Information
- Application Number
- CN202411343332.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
AI Technical Summary
The existing cellulose triboelectric materials have fire risks and complex chemical reactions during the production process, and their high flammability may lead to safety hazards. The existing preparation methods are complex, making it difficult to achieve simple and environmentally friendly flame retardant properties.
Cellulose nanofibers are prepared based on straw recycling resources, and combined with micro/sodium-scale two-dimensional flame retardant fillers, and the layered flame retardant cellulose nanofiber triboelectric positive electrode is constructed through fluid directional assembly technology to achieve triboelectric properties and Excellent combination of flame retardant properties.
An environmentally friendly flame-retardant cellulose nanogenerator that can maintain electrical output performance under high temperature and combustion damage conditions is realized, which simplifies the preparation process, reduces production costs, and improves the utilization rate of agricultural waste.
Smart Images

Figure CN119298709A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of triboelectric nanogenerators, and relates to an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator and a preparation method and application thereof. Background Art
[0002] With the growing demand for environmental friendliness and renewable energy, an emerging energy harvesting device, triboelectric nanogenerators (TENGs), has recently attracted widespread attention. The working principle of TENGs relies on electrostatic effect and friction induction effect. They can convert mechanical energy in the environment into electrical energy to provide power for wired or wireless devices. Triboelectric materials are the core components of TENGs. Most of the TENGs materials with excellent performance are non-renewable synthetic polymers. With the continuous growth of the economy, environmental protection has become a key factor in human survival and development. Effective measures must be taken to ensure that the impact of its production process on the environment is minimized. In order to achieve more environmentally friendly and sustainable technological development, the development of degradable or recyclable triboelectric materials is one of the key directions for the future development of TENGs. Therefore, it has become particularly urgent to find environmentally friendly and economical alternative materials. Cellulose nanofibers (CNFs) are regarded as an environmentally friendly triboelectric material with application prospects due to their excellent mechanical properties and biodegradability.
[0003] For example, the Chinese invention patent application of Guilin University of Technology, "A method for preparing a high-performance sisal nanocellulose membrane-based friction nanogenerator" (CN115021608A), discloses a method for preparing a high-performance sisal nanocellulose membrane-based friction nanogenerator, the preparation steps of which are as follows: (1) pretreating sisal fiber by hydrothermal reaction; (2) subjecting sisal cellulose to alkalization and etherification to obtain sisal carboxymethyl cellulose; (3) bleaching and hydrolyzing sisal cellulose to obtain sisal microcrystalline cellulose; (4) adding sisal carboxymethyl cellulose to sisal microcrystalline cellulose to prepare a sisal nanocellulose membrane; (5) assembling the sisal nanocellulose membrane with a triboelectrically negative material to prepare a friction nanogenerator.
[0004] However, in such technical research and patent literature using cellulose nanofibers, the important factor of fire safety in practical applications is often overlooked. The high flammability of cellulose may bring fire risks and pose serious safety hazards. Cellulose-based electronic devices may be damaged by combustion, resulting in power outages and being unable to work. At the same time, cellulose nanofibers also have the same safety risks in the production and preparation process. In addition, the existing preparation methods of cellulose triboelectric materials usually involve complex chemical reactions (Qingshan Duan, Zhijun Zhang, Jiamin Zhao, Juanxia He, Weiqing Peng, Ye Zhang, Tao Liu, Shuangfei Wang, Shuangxi Nie. Fire-retardant hydroxyapatite / cellulosic triboelectric materials for energy harvesting and sensing at extreme conditions. Nano Energy. 2023, 117, 108851.) and ultra-long reaction time (Jianjun Luo, Xue Shi, Pengfei Chen, Kai Han, Xunjia Li, Xia Cao, Zhong LinWang. Strong and flame-retardant wood-based triboelectric nanogenerators toward self-powered building fire protection. Materials Today Physics. 2022, 27, 100798.). Therefore, it is of great significance and challenge to develop environmentally friendly flame-retardant cellulose triboelectric materials that can be easily prepared. Summary of the invention
[0005] The purpose of the present invention is to solve the problems in the above-mentioned background technology and to provide an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator and its preparation method and application. The preparation method uses cellulose nanofibers prepared based on recycled resources such as straw as raw materials that can meet the requirements of fluid-directed self-assembly, and combines micro / nano-level two-dimensional flame-retardant fillers to form a flame-retardant cellulose nanofiber triboelectric positive electrode with a layered structure, thus realizing for the first time a triboelectric nanogenerator with excellent triboelectric properties and flame retardant properties.
[0006] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.
[0007] A method for preparing an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator mainly comprises the following steps:
[0008] (1) preparing 1 to 3 wt% of cellulose nanofibers into a nanofiber suspension, then adding 10 to 50% by weight of micro / nano-scale two-dimensional flame retardant fillers of cellulose nanofibers and mixing them evenly to obtain a fluid directional assembly liquid;
[0009] (2) The fluid directional assembly liquid obtained in step (1) is subjected to fluid directional assembly to obtain a flame-retardant cellulose nanofiber triboelectric film positive electrode, which is assembled with an electrode, a triboelectric negative electrode and a triboelectric nanogenerator support to form an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator.
[0010] In this article, the cellulose nanofibers in step (1) can be self-produced or directly obtained from the market. Those skilled in the art can select a suitable source of cellulose nanofibers based on cost and production process requirements.
[0011] In one technical solution, the cellulose nanofibers in step (1) are prepared by extracting recycled straw. Generally speaking, the recycled straw is natural crop straw recycled in the agricultural production process to meet the low-cost demand, such as any one or more of wheat straw, corn straw, rice straw, barley straw, cotton straw, rape straw, soybean straw, sugarcane straw, and buckwheat straw.
[0012] It should be noted that the above-mentioned cellulose nanofibers are prepared based on the extraction of recycled straw. The specific process / method for preparing cellulose nanofibers by extracting straw has relevant technical documents. Those skilled in the art can directly refer to the content in the relevant technical documents, or directly purchase cellulose nanofibers prepared based on straw extraction. It should be emphasized that in the embodiments of this invention, the cellulose nanofibers used are prepared based on straw extraction, but this is not the only designation or limitation on the source of cellulose nanofibers.
[0013] In order to better illustrate the present invention and provide a technical solution for reference, the cellulose nanofibers in step (1) are prepared based on straw extraction, which specifically includes the following steps:
[0014] (I) pre-treating straw to obtain cellulose by removing lignin based on an alkaline method;
[0015] (II) The cellulose obtained in step (I) is subjected to conventional treatment including homogenization to obtain cellulose nanofibers.
[0016] In the above technical scheme, in step (I), the straw is pretreated based on the alkaline method to remove lignin, and the straw is immersed in a chlorine-containing compound solution / sulfur-containing compound solution / peroxide solution or the above mixed solution to remove lignin, and then immersed in a strong alkaline hydroxide solution to remove hemicellulose.
[0017] Among them, the chlorine-containing compound solution is the chlorine-containing compound solution conventionally used for alkaline removal of lignin in industry / laboratory, which mainly plays the role of removing lignin. Those skilled in the art can refer to the existing technology and common knowledge in the field to prepare solutions of chlorine-containing compounds that can remove lignin.
[0018] In order to better illustrate the present invention and provide a preferred technical solution, the chlorine-containing compound solution is selected to include any one or more of sodium hypochlorite, potassium hypochlorite, calcium hypochlorite, sodium chlorite, potassium chlorite, chlorous acid, magnesium chlorite, calcium chlorite, barium chlorite, hypochlorous acid, chlorine dioxide, chloric acid, sodium chlorate, potassium chlorate, calcium chlorate, sodium perchlorate, calcium perchlorate, potassium perchlorate, and ammonium chloride as a solute to obtain a solution; and the solvent is generally water.
[0019] Among them, the sulfur-containing compound solution is the sulfur-containing compound solution conventionally used for alkaline removal of lignin in industry / laboratory, which mainly plays the role of removing lignin. Those skilled in the art can refer to the existing technology and common knowledge in the field to prepare solutions of sulfur-containing compounds that can remove lignin.
[0020] In order to better illustrate the present invention and provide a preferred technical solution, the sulfur-containing compound solution is selected to include any one or more of sulfurous acid, sodium sulfite, potassium sulfite, calcium sulfite, anhydrous sodium sulfite, sodium hyposulfite, sodium metabisulfite, and potassium persulfate as a solute to obtain a solution; and the solvent is generally water.
[0021] Among them, the peroxide solution is the peroxide solution conventionally used for alkaline removal of lignin in industry / laboratory, which mainly plays the role of removing lignin. Those skilled in the art can refer to the existing technology and common knowledge in the field to obtain the solution prepared by peroxide that can remove lignin.
[0022] In order to better illustrate the present invention and provide a preferred technical solution, the peroxide solution is selected to include any one or more of hydrogen peroxide, sodium peroxide, potassium peroxide, calcium peroxide, magnesium peroxide, zinc peroxide, and strontium peroxide as a solute; and the solvent is generally water.
[0023] Furthermore, the above-mentioned mixed solution is a mixed solution obtained by mixing any two or three of a chlorine-containing compound solution, a sulfur-containing compound solution, and a peroxide solution, and its specific solute selection is consistent with the selectable range of the above-mentioned chlorine-containing compound solution / sulfur-containing compound solution / peroxide solution.
[0024] Among them, the strong alkali hydroxide solution is the strong alkali hydroxide solution conventionally used in industry / laboratories, which mainly plays the role of removing hemicellulose. Those skilled in the art can refer to the existing technology and common knowledge in the field to obtain solutions prepared by strong alkali hydroxides that can remove hemicellulose.
[0025] In order to better illustrate the present invention and provide a preferred technical solution, the strong base hydroxide solution is selected to include any one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide, lithium hydroxide, cesium hydroxide, and barium hydroxide as a solute; and the solvent is generally water.
[0026] In the above technical solution, before the pretreatment in step (I), conventional raw material pretreatment can be carried out according to the straw conditions, such as cutting, washing, drying and other conventional treatments.
[0027] In the above technical solution, the homogenization treatment in step (II) is to further micronize and homogenize the cellulose using a homogenizer. In order to make the obtained cellulose nanofibers have better fluid-oriented assembly properties, in one preferred technical solution, the cellulose nanofibers obtained after the homogenization treatment in step (II) have an average length of 500 to 4000 nm and an average diameter of no more than 28 nm.
[0028] In one of the technical solutions, the outer diameter of the micro / nano-scale two-dimensional flame-retardant filler in step (1) is 0.5 to 50 μm.
[0029] In one of the technical solutions, the micro / nano-scale two-dimensional flame retardant filler in step (1) is any one or more of carbonate, silicate, sulfate, graphene, boron nitride, two-dimensional metal organic framework, and two-dimensional covalent organic framework.
[0030] The carbonate is the carbonate commonly used in industry / laboratories, which mainly plays a role in improving flame retardant properties. Those skilled in the art may refer to the existing technology and common knowledge in the field for carbonates that can be used as flame retardant fillers.
[0031] In order to better illustrate the present invention and provide a preferred technical solution, the carbonate is selected to include any one or more mixtures of calcite, aragonite, magnesite, dolomite, siderite, rhodochrosite, smithsonite, cerussite, strontium carbonate and witherite.
[0032] The silicate is the silicate commonly used in industry / laboratories, and it mainly plays the role of improving the flame retardant performance. Those skilled in the art may refer to the silicates that can be used as flame retardant fillers in the prior art and common knowledge in the field.
[0033] In order to better illustrate the present invention and provide a preferred technical solution, the silicate is selected to include any one or more mixtures of olivine, epidote, tourmaline, pyroxene, hornblende, mica, inorganic filler, feldspar and quartz.
[0034] The sulfate is the sulfate commonly used in industry / laboratories, and it mainly plays a role in improving flame retardant properties. Those skilled in the art may refer to the prior art and common knowledge in the art for sulfates that can be used as flame retardant fillers.
[0035] In order to better illustrate the present invention and provide a preferred technical solution, the sulfate is selected to include any one or more mixtures of calcium sulfate, barium sulfate, ferrous sulfate, cupric sulfate, potassium aluminum sulfate, sodium sulfate and aluminum sulfate.
[0036] The graphene is the graphene commonly used in industry / laboratories, which mainly plays a role in improving flame retardant properties. Those skilled in the art may refer to the prior art and common knowledge in the field for graphene that can be used as flame retardant fillers.
[0037] In order to better illustrate the present invention and provide a preferred technical solution, the graphene is selected to include any one or more mixtures of single-layer graphene, double-layer graphene, few-layer graphene, multi-layer graphene and thick-layer graphene.
[0038] The boron nitride is the boron nitride commonly used in industry / laboratories, which mainly plays a role in improving flame retardant properties. Those skilled in the art may refer to the prior art and common knowledge in the field for boron nitride that can be used as a flame retardant filler.
[0039] In order to better illustrate the present invention and provide a preferred technical solution, the boron nitride is selected to include any one or more mixtures of hexagonal boron nitride, cubic boron nitride, rhombohedral boron nitride, wurtzite boron nitride and amorphous boron nitride.
[0040] Among them, the two-dimensional metal organic framework is a two-dimensional metal organic framework commonly used in industry / laboratories, which mainly plays a role in improving flame retardant properties. Those skilled in the art can refer to the existing technology and common knowledge in the field for two-dimensional metal organic frameworks that can be used as flame retardant fillers.
[0041] In order to better illustrate the present invention and provide a preferred technical solution, the two-dimensional metal-organic framework is selected to include any one or more mixtures of an iron-based two-dimensional metal-organic framework, a cobalt-based two-dimensional metal-organic framework, a nickel-based two-dimensional metal-organic framework, a copper-based two-dimensional metal-organic framework and a zinc-based two-dimensional metal-organic framework.
[0042] Among them, the two-dimensional covalent organic framework is a two-dimensional covalent organic framework commonly used in industry / laboratories, which mainly plays a role in improving flame retardant properties. Those skilled in the art can refer to the existing technology and common knowledge in the field for two-dimensional covalent organic frameworks that can be used as flame retardant fillers.
[0043] In order to better illustrate the present invention and provide a technical solution for reference, the two-dimensional covalent organic framework is selected to include any one or more mixtures of a two-dimensional covalent organic framework based on imine connection, a two-dimensional covalent organic framework based on triazine connection, a two-dimensional covalent organic framework based on boric acid connection, a two-dimensional covalent organic framework based on chalcogen connection, and a two-dimensional covalent organic framework based on carbon-carbon bond connection.
[0044] In this article, the flame-retardant cellulose nanofiber triboelectric film positive electrode is obtained by fluid-directed assembly in step (2), wherein fluid-directed assembly is an assembly technology that relies on a fluid force field as a driving force. In the present invention, micro / nano-scale two-dimensional flame-retardant fillers need to be stacked in a directional manner under the action of a fluid field to form a layered structure, and cellulose nanofibers are coated therein as an interlayer. In order to achieve this purpose, fluid-directed assembly based on shear force is usually used.
[0045] Herein, in step (1), the cellulose nanofibers are prepared into a 1-3 wt% nanofiber suspension, wherein the solvent used for the preparation should be a fluid medium suitable for fluid-oriented assembly and will not dissolve the cellulose nanofibers, such as an aqueous solvent.
[0046] In order to better illustrate the present invention and provide a technical solution for reference, the fluid directional assembly in step (2) is based on a scraping method, and the process parameters of the scraping method include: applying the fluid directional assembly liquid on the substrate, the height of the scraper from the substrate is not higher than 3 mm, and the moving speed is not higher than 10 cm / s.
[0047] In one preferred technical solution, in order to further improve the assemblability of the fluid directional assembly solution, the cellulose nanofibers in step (1) are configured as a 1-2 wt% nanofiber suspension.
[0048] In one of the preferred technical schemes, in order to better balance the triboelectric properties and flame retardant properties of the prepared environmentally friendly flame retardant cellulose nanofiber triboelectric nanogenerator, the fluid directional assembly liquid in step (1) is a micro / nano-level two-dimensional flame retardant filler with 15 to 20% by mass of cellulose nanofibers.
[0049] In this article, the triboelectric negative electrode in step (2) is a conventional necessary component of a triboelectric nanogenerator. Those skilled in the art can directly refer to the negative electrode selection in the prior art literature in this field, or directly purchase conventional negative electrode products suitable for use as triboelectric nanogenerators. Generally speaking, under the premise of miniaturizing triboelectric nanogenerators, the triboelectric negative electrode in step (2) is preferably selected as a thin film negative electrode.
[0050] In one of the technical solutions, the material of the triboelectric negative electrode in step (2) includes any one of fluorinated ethylene propylene copolymer, polyvinylidene fluoride, polydimethylsiloxane, polyethylene terephthalate, polyimide, and polytetrafluoroethylene.
[0051] Herein, the electrode in step (2) is a conventional necessary component of a triboelectric nanogenerator. Those skilled in the art may directly refer to the electrode selection in the prior art literature in the field, or directly purchase conventional electrode products suitable as triboelectric nanogenerators.
[0052] In one of the technical solutions, the electrode in step (2) is a copper foil, and can be directly used as a substrate in the fluid-directed assembly process based on the doctor blade method in the above technical solution, so that the positive electrode of the flame-retardant cellulose nanofiber triboelectric film and the electrode are directly assembled through fluid-directed assembly.
[0053] Herein, the triboelectric nanogenerator support member described in step (2) is a conventional necessary component of the triboelectric nanogenerator. Those skilled in the art may directly refer to the support member selection in the prior art literature in the field, or directly purchase a conventional support member suitable as a triboelectric nanogenerator.
[0054] In one of the technical solutions, the triboelectric nanogenerator support member in step (2) is a support plate member made of acrylic material.
[0055] In this article, the flame-retardant cellulose nanofiber triboelectric film positive electrode is assembled with the electrode, the triboelectric negative electrode and the triboelectric nanogenerator support member in step (2) to form an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator. The assembly method can directly refer to the conventional triboelectric nanogenerator in the prior art, for example, the flame-retardant cellulose nanofiber triboelectric positive electrode is fixed on the electrode, and then the triboelectric negative electrode is fixed on the triboelectric nanogenerator support member respectively, and the electrode is connected to the wire to supply energy to the outside world.
[0056] In this article, the mixing, washing and drying all follow the conventional principles in chemical processes, and those skilled in the art can perform specific operations according to common knowledge.
[0057] On the other hand, the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator provided by the present invention is applied to the fields of self-powered sensing, triboelectric materials, biomass materials and fireproof materials.
[0058] The present invention has the following beneficial effects:
[0059] 1. The present invention provides an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator and its preparation method and application. The preparation method uses cellulose nanofibers prepared from recycled resources such as straw as a raw material that can meet the requirements of fluid-directed self-assembly, and combines micro / nano-level two-dimensional flame-retardant fillers to form a flame-retardant cellulose nanofiber triboelectric positive electrode with a layered structure, thus realizing for the first time a triboelectric nanogenerator with excellent triboelectric properties and flame retardant properties.
[0060] 2. The environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator prepared by the present invention, in one embodiment, has a finer size and a high specific surface area that provide effective sites for static charge accumulation. When the working frequency is 2Hz, the working pressure is 0.4kPa, and the working area is 4.0cm×4.0cm, its open circuit voltage, short circuit current, and transfer charge are 46V, 0.28μA, and 14.5nC, respectively. In particular, the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator embodiment provided by the present invention can maintain 60% of the initial voltage output even at 160°C; when the combustion damage area is 50%, it can still maintain 64% of the initial voltage output.
[0061] 3. In one of the technical solutions, the cellulose nanofiber raw material required by the present invention comes from straw, which is cheap and easily available. A matching preparation method is provided, which is simple to operate and does not require complex and expensive instruments and equipment in the process. It also improves the high value-added utilization rate of agricultural waste straw, making the technology for preparing environmentally friendly flame-retardant cellulose nanofiber friction electric nanogenerators more economical and environmentally friendly, and has prospects for industrial application and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a flow chart for preparing the flame-retardant cellulose nanofiber triboelectric film positive electrode in Examples 1 to 5 of the present invention.
[0063] Figure 2The working principle diagram of the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator in Examples 1 to 5 of the present invention. Among them, step (I) shows the static state after contact, step (II) shows the separation state, step (III) shows the static state after separation to a certain distance, and step (IV) shows the state of starting contact; TOCN / IF corresponds to the positive electrode of the flame-retardant cellulose nanofiber triboelectric film in the embodiment, FEP corresponds to the triboelectric negative electrode in the embodiment, and Cu corresponds to the copper foil electrode in the embodiment.
[0064] Figure 3 The open circuit voltage, short circuit current and transfer charge relationship comparison diagram of the samples prepared in Examples 1 to 5 of the present invention are shown in Figure a, Figure b is a short circuit current comparison diagram of the samples in Examples 1 to 5, and Figure c is a transfer charge relationship comparison diagram of the samples in Examples 1 to 5.
[0065] Figure 4 The figure is a comparison diagram of the relationship between the contact pressure, contact area, contact frequency and open circuit voltage of the samples prepared in Example 3 of the present invention. Among them, Figure a is a comparison diagram of the relationship between the contact pressure and the open circuit voltage of the samples in Example 3, Figure b is a comparison diagram of the relationship between the contact area and the open circuit voltage of the samples in Example 3, and Figure c is a comparison diagram of the relationship between the contact frequency and the open circuit voltage of the samples in Example 3.
[0066] Figure 5 The voltage and power curves of the samples prepared in Example 3 of the present invention under different external loads and the cycle stability test result diagram are shown in Figure a. Figure b is a power curve of the samples in Example 3 under different external loads, and Figure c is a cycle stability test result diagram of the samples in Example 3.
[0067] Figure 6 The schematic diagram, charging curve and power supply curve of the sample prepared in Example 3 of the present invention for powering a smart home are shown in Figure a, Figure b is a charging curve of a 1-100 μF capacitor of the sample in Example 3, and Figure c is a power supply curve of a calculator through a capacitor of the sample in Example 3 of the present invention.
[0068] Figure 7 This is a comparison chart of the combustion tests of the samples prepared in Examples 1 to 5 of the present invention and Comparative Example 1.
[0069] Figure 8 The cone calorimetry test results of the samples prepared in Example 3 and Comparative Example 1 of the present invention are shown in Figure a, which is a heat release rate comparison chart, Figure b is a total heat release comparison chart, Figure c is a smoke release rate comparison chart, and Figure d is a total smoke release comparison chart.
[0070] Fig. 9 The power supply capacity evaluation diagram of the samples prepared in Example 3 and Comparative Example 1 of the present invention in a fire environment. Among them, Figure a is a relative voltage output diagram of the sample of Example 3 at different temperatures, Figure b is a relative voltage output comparison diagram of the samples of Example 3 and Comparative Example 1 at different vertical burning times, Figure c is a relative voltage output comparison diagram of the samples of Example 3 and Comparative Example 1 at different horizontal burning times, and Figure d is a relative voltage output diagram of the sample of Example 3 at different damaged areas.
[0071] Fig.10 This is a diagram showing a self-powered wireless fire monitoring system composed of the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator prepared in Example 3 of the present invention, a smart phone, a multimeter and a microcontroller.
[0072] Fig.11 The wireless communication concept verification application demonstration diagram of the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator prepared in Example 3 of the present invention is shown in Figure a, which is a schematic diagram of self-powered wireless fire monitoring, Figure b is a schematic diagram of a microcontroller loaded with a buzzer module and a Bluetooth module, Figure c is a working demonstration diagram of the self-powered wireless fire monitoring system before the combustion test, Figure d is a 20s flame combustion test display diagram, and Figure e is a working demonstration diagram after the combustion test.
[0073] Fig.12 This is a flow chart of the recovery of the flame-retardant cellulose nanofiber triboelectric film positive electrode prepared in Examples 1 to 5 of the present invention. DETAILED DESCRIPTION
[0074] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.
[0075] A method for preparing an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator mainly comprises the following steps:
[0076] (1) preparing 1 to 3 wt% of cellulose nanofibers into a nanofiber suspension, then adding 10 to 50% by weight of micro / nano-scale two-dimensional flame retardant fillers of cellulose nanofibers and mixing them evenly to obtain a fluid directional assembly liquid;
[0077] (2) The fluid directional assembly liquid obtained in step (1) is subjected to fluid directional assembly to obtain a flame-retardant cellulose nanofiber triboelectric film positive electrode, which is assembled with an electrode, a triboelectric negative electrode and a triboelectric nanogenerator support to form an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator.
[0078] In this article, the cellulose nanofibers in step (1) can be self-produced or directly obtained from the market. Those skilled in the art can select a suitable source of cellulose nanofibers based on cost and production process requirements.
[0079] In one embodiment, the cellulose nanofibers in step (1) are prepared by extracting recycled straw. Generally speaking, the recycled straw is natural crop straw recycled in the agricultural production process to meet the low cost demand, such as any one or more of wheat straw, corn straw, rice straw, barley straw, cotton straw, rape straw, soybean straw, sugarcane straw, and buckwheat straw.
[0080] It should be noted that the above-mentioned cellulose nanofibers are prepared based on the extraction of recycled straw. The specific process / method for preparing cellulose nanofibers by extracting straw has relevant technical documents. Those skilled in the art can directly refer to the content in the relevant technical documents, or directly purchase cellulose nanofibers prepared based on straw extraction. It should be emphasized that in the embodiments of this invention, the cellulose nanofibers used are prepared based on straw extraction, but this is not the only designation or limitation on the source of cellulose nanofibers.
[0081] In order to better illustrate the present invention and provide an embodiment for reference, the cellulose nanofibers in step (1) are prepared based on straw extraction, specifically comprising the following steps:
[0082] (I) pre-treating straw to obtain cellulose by removing lignin based on an alkaline method;
[0083] (II) The cellulose obtained in step (I) is subjected to conventional treatment including homogenization to obtain cellulose nanofibers.
[0084] In the above embodiment, in step (I), the straw is pretreated based on alkaline method to remove lignin, which is to soak the straw in a chlorine-containing compound solution / sulfur-containing compound solution / peroxide solution or the above mixed solution to remove lignin, and then soak it in a strong alkaline hydroxide solution to remove hemicellulose.
[0085] Among them, the chlorine-containing compound solution is the chlorine-containing compound solution conventionally used for alkaline removal of lignin in industry / laboratory, which mainly plays the role of removing lignin. Those skilled in the art can refer to the existing technology and common knowledge in the field to prepare solutions of chlorine-containing compounds that can remove lignin.
[0086] In order to better illustrate the present invention and provide a preferred embodiment, the chlorine-containing compound solution is selected to include any one or more of sodium hypochlorite, potassium hypochlorite, calcium hypochlorite, sodium chlorite, potassium chlorite, chlorous acid, magnesium chlorite, calcium chlorite, barium chlorite, hypochlorous acid, chlorine dioxide, chloric acid, sodium chlorate, potassium chlorate, calcium chlorate, sodium perchlorate, calcium perchlorate, potassium perchlorate, and ammonium chloride as a solute to obtain a solution; and the solvent is generally water.
[0087] Among them, the sulfur-containing compound solution is the sulfur-containing compound solution conventionally used for alkaline removal of lignin in industry / laboratory, which mainly plays the role of removing lignin. Those skilled in the art can refer to the existing technology and common knowledge in the field to prepare solutions of sulfur-containing compounds that can remove lignin.
[0088] In order to better illustrate the present invention and provide a preferred embodiment, the sulfur-containing compound solution is selected to include any one or more of sulfurous acid, sodium sulfite, potassium sulfite, calcium sulfite, anhydrous sodium sulfite, sodium hyposulfite, sodium metabisulfite, and potassium persulfate as a solute to obtain a solution; and the solvent is generally water.
[0089] Among them, the peroxide solution is the peroxide solution conventionally used for alkaline removal of lignin in industry / laboratory, which mainly plays the role of removing lignin. Those skilled in the art can refer to the existing technology and common knowledge in the field to obtain the solution prepared by peroxide that can remove lignin.
[0090] In order to better illustrate the present invention and provide a preferred embodiment, the peroxide solution is selected to include any one or more of hydrogen peroxide, sodium peroxide, potassium peroxide, calcium peroxide, magnesium peroxide, zinc peroxide, and strontium peroxide as a solute; and the solvent is generally water.
[0091] Furthermore, the above-mentioned mixed solution is a mixed solution obtained by mixing any two or three of a chlorine-containing compound solution, a sulfur-containing compound solution, and a peroxide solution, and its specific solute selection is consistent with the selectable range of the above-mentioned chlorine-containing compound solution / sulfur-containing compound solution / peroxide solution.
[0092] Among them, the strong alkali hydroxide solution is the strong alkali hydroxide solution conventionally used in industry / laboratories, which mainly plays the role of removing hemicellulose. Those skilled in the art can refer to the existing technology and common knowledge in the field to obtain solutions prepared by strong alkali hydroxides that can remove hemicellulose.
[0093] In order to better illustrate the present invention and provide a preferred embodiment, the strong base hydroxide solution is selected to include any one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide, lithium hydroxide, cesium hydroxide, and barium hydroxide as a solute; and the solvent is generally water.
[0094] In the above embodiment, before the pretreatment in step (I), conventional raw material pretreatment may be performed according to the straw condition, such as cutting, washing, drying and other conventional treatments.
[0095] In the above embodiment, the homogenization treatment in step (II) is to further micronize and homogenize the cellulose using a homogenizer. In order to make the obtained cellulose nanofibers have better fluid-oriented assemblability, in one preferred embodiment, the cellulose nanofibers obtained after the homogenization treatment in step (II) have an average length of 500 to 4000 nm and an average diameter of no more than 28 nm.
[0096] In one embodiment, the outer diameter of the micro / nano-scale two-dimensional flame retardant filler in step (1) is 0.5 to 50 μm.
[0097] In one embodiment, the micro / nano-scale two-dimensional flame retardant filler in step (1) is any one or more of carbonate, silicate, sulfate, graphene, boron nitride, two-dimensional metal organic framework, and two-dimensional covalent organic framework.
[0098] The carbonate is the carbonate commonly used in industry / laboratories, which mainly plays a role in improving flame retardant properties. Those skilled in the art may refer to the existing technology and common knowledge in the field for carbonates that can be used as flame retardant fillers.
[0099] In order to better illustrate the present invention and provide a preferred embodiment, the carbonate is selected to include any one or more mixtures of calcite, aragonite, magnesite, dolomite, siderite, rhodochrosite, smithsonite, cerussite, strontium carbonate and witherite.
[0100] The silicate is the silicate commonly used in industry / laboratories, and it mainly plays the role of improving the flame retardant performance. Those skilled in the art may refer to the silicates that can be used as flame retardant fillers in the prior art and common knowledge in the field.
[0101] In order to better illustrate the present invention and provide a preferred embodiment, the silicate is selected to include any one or more mixtures of olivine, epidote, tourmaline, pyroxene, hornblende, mica, inorganic filler, feldspar and quartz.
[0102] The sulfate is the sulfate commonly used in industry / laboratories, and it mainly plays a role in improving flame retardant properties. Those skilled in the art may refer to the prior art and common knowledge in the art for sulfates that can be used as flame retardant fillers.
[0103] In order to better illustrate the present invention and provide a preferred embodiment, the sulfate is selected to include any one or more mixtures of calcium sulfate, barium sulfate, ferrous sulfate, copper sulfate, potassium aluminum sulfate, sodium sulfate and aluminum sulfate.
[0104] The graphene is the graphene commonly used in industry / laboratories, which mainly plays a role in improving flame retardant properties. Those skilled in the art may refer to the prior art and common knowledge in the field for graphene that can be used as flame retardant fillers.
[0105] In order to better illustrate the present invention and provide a preferred embodiment, the graphene is selected to include any one or more mixtures of single-layer graphene, double-layer graphene, few-layer graphene, multi-layer graphene and thick-layer graphene.
[0106] The boron nitride is the boron nitride commonly used in industry / laboratories, which mainly plays a role in improving flame retardant properties. Those skilled in the art may refer to the prior art and common knowledge in the field for boron nitride that can be used as a flame retardant filler.
[0107] In order to better illustrate the present invention and provide a preferred embodiment, the boron nitride is selected to include any one or more mixtures of hexagonal boron nitride, cubic boron nitride, rhombohedral boron nitride, wurtzite boron nitride and amorphous boron nitride.
[0108] Among them, the two-dimensional metal organic framework is a two-dimensional metal organic framework commonly used in industry / laboratories, which mainly plays a role in improving flame retardant properties. Those skilled in the art can refer to the existing technology and common knowledge in the field for two-dimensional metal organic frameworks that can be used as flame retardant fillers.
[0109] In order to better illustrate the present invention and provide a preferred embodiment, the two-dimensional metal-organic framework is selected to include any one or more mixtures of an iron-based two-dimensional metal-organic framework, a cobalt-based two-dimensional metal-organic framework, a nickel-based two-dimensional metal-organic framework, a copper-based two-dimensional metal-organic framework and a zinc-based two-dimensional metal-organic framework.
[0110] Among them, the two-dimensional covalent organic framework is a two-dimensional covalent organic framework commonly used in industry / laboratories, which mainly plays a role in improving flame retardant properties. Those skilled in the art can refer to the existing technology and common knowledge in the field for two-dimensional covalent organic frameworks that can be used as flame retardant fillers.
[0111] In order to better illustrate the present invention and provide a preferred embodiment, the two-dimensional covalent organic framework is selected to include any one or more mixtures of a two-dimensional covalent organic framework based on imine connection, a two-dimensional covalent organic framework based on triazine connection, a two-dimensional covalent organic framework based on boric acid connection, a two-dimensional covalent organic framework based on chalcogen connection, and a two-dimensional covalent organic framework based on carbon-carbon bond connection.
[0112] In this article, the flame-retardant cellulose nanofiber triboelectric film positive electrode is obtained by fluid directional assembly as described in step (2), wherein the fluid directional assembly is an assembly technology that relies on a fluid force field as a driving force. In the present invention, micro / nano-scale two-dimensional flame-retardant fillers need to be directional stacked under the action of a fluid field to form a layered structure, and cellulose nanofibers are coated therein as an interlayer. In order to achieve this purpose, it is usually achieved by fluid directional assembly based on shear force.
[0113] Herein, in step (1), the cellulose nanofibers are prepared into a 1-3 wt% nanofiber suspension, wherein the solvent used for the preparation should be a fluid medium suitable for fluid-oriented assembly and will not dissolve the cellulose nanofibers, such as an aqueous solvent.
[0114] In order to better illustrate the present invention and provide an implementation method for reference, the fluid directional assembly in step (2) is based on a scraping method, and the process parameters of the scraping method include: applying the fluid directional assembly liquid to the substrate, the height of the scraper from the substrate is not higher than 3 mm, and the moving speed is not higher than 10 cm / s.
[0115] In one preferred embodiment, in order to further improve the assemblability of the fluid-oriented assembly solution, the cellulose nanofibers in step (1) are configured as a 1-2 wt% nanofiber suspension.
[0116] In one of the preferred embodiments, in order to better balance the triboelectric properties and flame retardant properties of the prepared environmentally friendly flame retardant cellulose nanofiber triboelectric nanogenerator, the fluid directional assembly liquid in step (1) is a micro / nano-level two-dimensional flame retardant filler with 15 to 20% by mass of cellulose nanofibers.
[0117] In this article, the triboelectric negative electrode in step (2) is a conventional necessary component of a triboelectric nanogenerator. Those skilled in the art can directly refer to the negative electrode selection in the prior art literature in this field, or directly purchase a conventional negative electrode product suitable for use as a triboelectric nanogenerator. Generally speaking, under the premise of miniaturizing a triboelectric nanogenerator, in one embodiment, the triboelectric negative electrode in step (2) is preferably selected as a thin film negative electrode.
[0118] In one embodiment, the material of the triboelectric negative electrode in step (2) includes any one of fluorinated ethylene propylene copolymer, polyvinylidene fluoride, polydimethylsiloxane, polyethylene terephthalate, polyimide, and polytetrafluoroethylene.
[0119] Herein, the electrode in step (2) is a conventional necessary component of a triboelectric nanogenerator. Those skilled in the art may directly refer to the electrode selection in the prior art literature in the field, or directly purchase conventional electrode products suitable as triboelectric nanogenerators.
[0120] In one embodiment, the electrode in step (2) is a copper foil, and can be directly used as a substrate in the fluid directional assembly process based on the doctor blade method in the above technical solution, so that the positive electrode of the flame-retardant cellulose nanofiber triboelectric film and the electrode are directly assembled through the fluid directional assembly.
[0121] Herein, the triboelectric nanogenerator support member described in step (2) is a conventional necessary component of the triboelectric nanogenerator. Those skilled in the art may directly refer to the support member selection in the prior art literature in the field, or directly purchase a conventional support member suitable as a triboelectric nanogenerator.
[0122] In one embodiment, the triboelectric nanogenerator support member in step (2) is a support plate member made of acrylic material.
[0123] In this article, the flame-retardant cellulose nanofiber triboelectric film positive electrode is assembled with the electrode, the triboelectric negative electrode and the triboelectric nanogenerator support member in step (2) to form an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator. The assembly method can directly refer to the conventional triboelectric nanogenerator in the prior art, for example, the flame-retardant cellulose nanofiber triboelectric positive electrode is fixed on the electrode, and then the triboelectric negative electrode is fixed on the triboelectric nanogenerator support member respectively, and the electrode is connected to the wire to supply energy to the outside world.
[0124] In this article, the mixing, washing and drying all follow the conventional principles in chemical processes, and those skilled in the art can perform specific operations according to common knowledge.
[0125] On the other hand, the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator provided by the present invention is applied to the fields of self-powered sensing, triboelectric materials, biomass materials and fireproof materials.
[0126] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.
[0127] Example
[0128] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.
[0129] 1. Raw materials
[0130] Corn stalks were purchased from commercial sources.
[0131] Sodium chlorite was purchased from Aladdin Chemical Co., Ltd., Shanghai, China; sodium hydroxide and glacial acetic acid were purchased from Chengdu Kelong Chemical Reagent Co., Ltd.; these reagents were used without any further purification.
[0132] The micro / nano-scale two-dimensional flame retardant filler is titanium mica with an outer diameter of 30 μm, purchased from Kuncai Material Technology Co., Ltd.; the electrode is copper foil with a thickness of 100 μm; and the triboelectric negative electrode is a fluorinated ethylene propylene copolymer film with a thickness of 200 μm.
[0133] 2. Preparation method
[0134] (1) adding cellulose nanofibers into deionized water to prepare a 1 wt% nanofiber suspension, and then adding 10 to 50% by weight of micro / nano-scale two-dimensional flame retardant fillers of the cellulose nanofibers and mixing them evenly to prepare a fluid directional assembly liquid;
[0135] The cellulose nanofibers are prepared by extracting corn stalks, and specifically include the following steps:
[0136] (I) 50 g corn stalks were soaked in a 1% sodium chlorite aqueous solution (adjusted to pH 3 with glacial acetic acid) at a liquid-solid ratio of 30 mL:1 g, and stirred at 40°C for 24 h on a magnetic stirring platform. After the soaking, the product was washed with clean water until neutral, and then soaked in a 1% sodium hydroxide aqueous solution at a liquid-solid ratio of 24 mL:1 g, and stirred at 90°C for 24 h on a magnetic stirring platform. After the soaking, the product was washed with clean water until neutral to obtain high-purity corn stalk cellulose, which was dried at 60°C and ground with a grinder at 30,000 r / min for 2 min to obtain fluffy corn stalk cellulose;
[0137] (II) preparing cellulose nanofibers by homogenizing the fluffy corn stalk cellulose obtained in step (I) using a homogenizer at a pressure of 800 bar, wherein the average length of the obtained cellulose nanofibers is 3000±100 nm and the average diameter is 22.6±5.6 nm;
[0138] (2) applying the fluid directional assembly liquid obtained in step (1) onto a copper foil electrode, and obtaining a flame-retardant cellulose nanofiber triboelectric film positive electrode by fluid directional assembly, wherein the fluid directional assembly is based on a doctor blade coating process, and the process parameters of the doctor blade coating process include: a height of the doctor blade from the copper foil of 2 mm, and a moving speed of 1 cm / s;
[0139] The flame-retardant cellulose nanofiber triboelectric film positive electrode is assembled with the copper foil electrode, the triboelectric negative electrode and the triboelectric nanogenerator support to form an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator, and the external energy supply is tested by connecting the electrodes with wires.
[0140] Example 1
[0141] Example 1 is prepared with reference to the above-mentioned "2. Preparation method", wherein 50% by weight of micro / nano-level two-dimensional flame retardant filler of cellulose nanofibers is added in step (1), and finally an environmentally friendly flame retardant cellulose nanofiber triboelectric nanogenerator sample is prepared.
[0142] Example 2
[0143] Example 2 is prepared with reference to the above “2. Preparation method”, wherein 25% by weight of micro / nano-level two-dimensional flame retardant filler of cellulose nanofibers is added in step (1), and finally an environmentally friendly flame retardant cellulose nanofiber triboelectric nanogenerator sample is prepared.
[0144] Example 3
[0145] Example 3 is prepared with reference to the above “2. Preparation method”, wherein 16.67% by mass of cellulose nanofibers are added as micro / nano-level two-dimensional flame retardant fillers in step (1), and finally an environmentally friendly flame retardant cellulose nanofiber triboelectric nanogenerator sample is prepared.
[0146] Example 4
[0147] Example 4 is prepared with reference to the above “2. Preparation method”, wherein 12.5% by mass of micro / nano-level two-dimensional flame retardant filler of cellulose nanofibers is added in step (1), and finally an environmentally friendly flame retardant cellulose nanofiber triboelectric nanogenerator sample is prepared.
[0148] Example 5
[0149] Example 5 is prepared with reference to the above “2. Preparation method”, wherein 10% by mass of micro / nano-level two-dimensional flame retardant filler of cellulose nanofibers is added in step (1), and finally an environmentally friendly flame retardant cellulose nanofiber triboelectric nanogenerator sample is prepared.
[0150] Comparative Example 1
[0151] Comparative Example 1 was prepared with reference to the above “2. Preparation method”, but no micro / nano-scale two-dimensional flame retardant filler was added in step (1), and finally a cellulose nanofiber triboelectric nanogenerator comparison sample was prepared.
[0152] 3. Test methods
[0153] (1) Use scanning electron microscopy (SEM, Prox, Phenom word) to characterize the morphology of the samples.
[0154] (2) The chemical structure was measured using Fourier transform infrared spectrometer (FT-IR, Nicolet 6700, ThermoFisherScientific).
[0155] (3) The crystallization was characterized using X-ray powder diffractometer (XRD6100).
[0156] (4) X-ray photoelectron spectrometer (K-Alpha, ThermoFisher Scientific) was used to characterize the element distribution on the sample surface.
[0157] (5) The thermal stability was tested using a thermogravimetric analyzer (TGA 5500, TA) at a rate of 20 °C / min in a N2 atmosphere at a temperature ranging from 50 to 700 °C.
[0158] (6) The zeta potential of cellulose nanofibers was characterized using a Malvern Zetasizer (ZEN3690, Malvern).
[0159] (7) Dynamic rheometer (Discovery HR-2, TA) was used to characterize the viscosity.
[0160] (8) Ignite the sample with an alcohol lamp and record the combustion process.
[0161] (9) According to ISO 5660-1, the pressure was measured at 35 kW / m on a cone calorimeter (iCone Plus, Fire Testing Technology). 2 Cone calorimeter tests were performed at a heat flux of 1.5 %.
[0162] (10) The output voltage, current and charge were measured using an electrometer (Keithley Model 6514).
[0163] 4. Test results
[0164] The fluid directional assembly fluid prepared in Examples 1 to 5 is a disordered structure formed by a continuous cross-linked network of cellulose nanofibers (TOCN) encapsulating a micro / nano-scale two-dimensional flame retardant filler, which has high viscosity at low shear rates and can maintain uniformity and stability on the substrate. Then, at high shear rates, the fluid directional assembly fluid has lower viscosity and better flow properties. During the preparation process, the fluid directional assembly fluid is horizontally stretched and vertically compressed under shear, resulting in the stratification and directional stacking of the micro / nano-scale two-dimensional flame retardant filler, such as Figure 1 shown.
[0165] The chain segments inside cellulose cannot provide effective sites for induced static electricity accumulation, while the finer size and high specific surface area of cellulose nanofibers provide effective sites for accumulating more static electricity. The effects of the structural characteristics of the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator provided by the present invention on the triboelectric output performance were explored. Figure 2 The working principle of the sample in the embodiment in single electrode mode is shown.
[0166] like Figure 3 As shown, increasing the amount of cellulose nanofibers added will produce higher open circuit voltage, short circuit current and transfer charge. Specifically, for the sample in Example 1, the open circuit voltage and short circuit current are 26V and 0.15μA, respectively, and the transfer charge is 8nC; for the sample in Example 3, the open circuit voltage and short circuit current are 32V and 0.2μA, respectively, and the transfer charge is 13nC; for the sample in Example 5, the open circuit voltage and short circuit current are 46V and 0.28μA, respectively, and the transfer charge is significantly increased to 14.5nC. Under the same conditions and the same cross-sectional area, increasing the amount of cellulose nanofibers will increase the effective site contribution of the friction layer, which is more conducive to the accumulation of static charge. In addition, as Figure 4As shown, for the sample prepared in Example 3, due to the generation of more transferred electrons, increasing the pressure and contact area will cause the open circuit voltage to increase from 32 V to 44 V and from 32 V to 406 V respectively. When the frequency increases from 1 Hz to 2.5 Hz, the open circuit voltage remains stable.
[0167] like Figure 5 As shown, the output voltage and power are measured at different external resistances. According to Ohm's law, increasing R will promote an increase in voltage but will result in a decrease in current. At 70MΩ, the maximum P reaches 8μW. Importantly, the sample of Example 3 can produce a stable electrical output over more than 6000 cycles.
[0168] like Figure 6 As shown, an external circuit is further designed to provide continuous power to small electronic devices. The environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator provided by the present invention can convert AC power into DC power by connecting a full-wave rectifier bridge. Capacitors with different capacitances (1μF, 22μF, 47μF and 100μF) can be charged by the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator. The environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator integrated with a 100μF capacitor can be used as a wearable energy supply system for small electronic devices; 310s charging can drive a calculator to work for 64s. These results show that the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator provided by the present invention has good self-powered sensing performance and energy supply capability, and has the potential to be integrated into buildings and household facilities.
[0169] The environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator with a "brick and mortar" structure formed by cellulose nanofibers (TOCN) and micro / nano-scale two-dimensional flame-retardant fillers can isolate the transfer of oxygen to the internal substrate, thereby achieving flame-retardant protection of the substrate. Figure 7 As shown in the horizontal burning test, the sample of comparative example 1 caught fire after being exposed to the fire for 10 seconds. In contrast, the sample of example 3 was able to extinguish itself within 3 seconds even after being exposed to the fire for 20 seconds. According to the cone calorimetry test results ( Figure 8 ), compared with the sample of comparative example 1 (258kW / m 2 ) compared to Example 3, the sample showed a significantly lower heat release rate (172 kW / m 2 ), which means a lower fire growth rate. It can be seen that the time to reach the peak of total heat release of the sample in Example 3 is longer than that of the control group. Importantly, the sample in Example 3 (0.02m 2 / s and 30m 2 / m 2 )'s peak smoke release rate and total smoke release were compared with the ratio (0.005m 2 / s and 21m 2 / m 2 ) were reduced by about 75% and 23%, which shows that the brick-mud structure formed by cellulose nanofibers (TOCN) and micro / nano-scale two-dimensional flame retardant fillers has excellent smoke suppression performance and significantly reduces the harm of smoke to human health.
[0170] like Fig. 9 As shown, the power supply capacity of the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator in a fire environment was further evaluated, and it was found that the output voltage of the sample of Example 3 decreased with increasing temperature, which was due to the decrease in surface charge density caused by electron thermionic emission, but it could maintain 60% of its initial output even at 160°C. In addition, even when the damage area was 50%, the sample of Example 3 could still convert mechanical energy into electrical energy, which was 64% of the initial electrical output. Based on the fact that the sample of Comparative Example 1 was completely destroyed after burning for 15 seconds, it showed no ability to generate any electrical output. In contrast, even after burning horizontally and vertically for 20 seconds, the sample of Example 3 still maintained 69% and 45% of the initial voltage, respectively, showing excellent triboelectric and flame retardant properties.
[0171] The operating mechanism of the self-powered wireless fire monitoring system based on the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator provided by the present invention is as follows: Fig.10 The system consists of an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator, a microcontroller, a buzzer module, a Bluetooth module, and a smartphone. A proof-of-concept application demonstration of wireless communication between trapped people and rescue agencies in fire emergencies based on an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator is shown in Figure 1. Fig.11 As shown, when encountering extreme accidents, trapped people can tap the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator to convert mechanical energy into electrical signals. After signal acquisition and processing by the microcontroller, the buzzer module emits continuous beeps, and the alarm signal is wirelessly transmitted to the smartphone via Bluetooth. It is worth noting that the system exhibits a fast response time (330ms) in the absence of fire attack, and can still work after burning for 20 seconds, with a response time within 1 second.
[0172] The recyclability of triboelectric materials is an attractive feature to effectively alleviate serious environmental problems and resource waste. We have comprehensively explored the recycling process of the flame-retardant cellulose nanofiber triboelectric film cathode in the present invention. The scrapped flame-retardant cellulose nanofiber triboelectric film cathode can be dispersed in water after shearing, and the physical cross-linked network can be reorganized after stirring, avoiding toxic reagents and complicated recycling processes ( Fig.12 ).
[0173] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator, characterized in that The main steps include: (1) preparing 1 to 3 wt% of cellulose nanofibers into a nanofiber suspension, then adding 10 to 50% by weight of micro / nano-scale two-dimensional flame retardant fillers of cellulose nanofibers and mixing them evenly to obtain a fluid directional assembly liquid; (2) The fluid directional assembly liquid obtained in step (1) is subjected to fluid directional assembly to obtain a flame-retardant cellulose nanofiber triboelectric film positive electrode, which is assembled with an electrode, a triboelectric negative electrode and a triboelectric nanogenerator support to form an environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator.
2. The preparation method according to claim 1, characterized in that: The cellulose nanofibers in step (1) are prepared based on straw extraction, which specifically includes the following steps: (I) pre-treating straw to obtain cellulose by removing lignin based on an alkaline method; (II) subjecting the cellulose obtained in step (I) to a homogenization treatment to obtain cellulose nanofibers.
3. The preparation method according to claim 1, characterized in that: The cellulose nanofibers in step (1) are configured as a 1-2 wt% nanofiber suspension.
4. The preparation method according to claim 1, characterized in that: The fluid directional assembly liquid in step (1) is a micro / nano-level two-dimensional flame retardant filler added with 15-20% by weight of cellulose nanofibers.
5. The preparation method according to claim 1, characterized in that: The fluid directional assembly in step (2) is based on a scraping method, and the process parameters of the scraping method include: applying the fluid directional assembly liquid on the substrate, the height of the scraper from the substrate is not higher than 3mm, and the moving speed is not higher than 10cm / s.
6. The preparation method according to claim 1, characterized in that: The micro / nano-scale two-dimensional flame retardant filler in step (1) is any one or more of carbonate, silicate, sulfate, graphene, boron nitride, two-dimensional metal organic framework, and two-dimensional covalent organic framework.
7. The preparation method according to claim 1, characterized in that: The material of the triboelectric negative electrode in step (2) includes any one of fluorinated ethylene propylene copolymer, polyvinylidene fluoride, polydimethylsiloxane, polyethylene terephthalate, polyimide, and polytetrafluoroethylene.
8. The preparation method according to claim 1 or 2, characterized in that: The cellulose nanofibers have an average length of 500 to 4000 nm and an average diameter of no more than 28 nm. 9 . The environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator prepared by the method for preparing the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator according to claim 1 .
10. Application of the environmentally friendly flame-retardant cellulose nanofiber triboelectric nanogenerator as claimed in claim 9 in the fields of self-powered sensing, triboelectric materials, biomass materials and fireproof materials.
Citation Information
Patent Citations
Preparation method of high-performance sisal hemp nano-cellulose membrane-based friction nano-generator
CN115021608A
Cited By
Preparation method of high-performance rope with flame-retardant, waterproof, anti-cutting and self-powered health monitoring functions
CN120759045A